MtDNA deletions and aging - Sprason, Charlotte; Tucker, Trudy; Clancy, David (Frontiers in Aging, 2024)
Aging is the major risk factor in most of the leading causes of mortality worldwide, yet its fundamental causes mostly remain unclear. One of the clear hallmarks of aging is mitochondrial dysfunction. Mitochondria are best known for their roles in cellular energy generation, but they are also critical biosynthetic and signaling organelles. They also undergo multiple changes with organismal age, including increased genetic errors in their independent, circular genome. A key group of studies looking at mice with increased mtDNA mutations showed that premature aging phenotypes correlated with increased deletions but not point mutations. This generated an interest in mitochondrial deletions as a potential fundamental cause of aging. However, subsequent studies in different models have yielded diverse results. This review summarizes the research on mitochondrial deletions in various organisms to understand their possible roles in causing aging while identifying the key complications in quantifying deletions across all models.